2021
DOI: 10.1007/s00605-021-01546-4
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Flag-transitive block designs and unitary groups

Abstract: In this note, we cover a gap in the proof of [2, Proposition 4.3]. In conclusion, Theorem 1.1 in [2] is revisited: if D is a 2-design with gcd(r , λ) = 1 and G is a flag-transitive almost simple automorphism group of D whose socle is PSU (n, q) with (n, q) = (3, 2), then D belongs to one of the three infinite families of Hermitian unitals, Witt-Bose-Shrikhande spaces and 2-designs with parameters (q 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Since then a special attention was given to the case λ > 1. A classification of the flag-transitive 2-designs with gcd(r, λ) = 1, λ > 1 and G AΓL 1 (q), where r is the replication number of D, has been announced by Alavi, Biliotti, Daneshkakh, Montinaro, Zhou and their collaborators in [2] and proven in [3], [4], [5], [9], [10], [8], [16], [17], [42], [52], [55], [56], [57], [58], [59], [60] and [61]. Moreover, recently the flag-transitive 2-designs with λ = 2 have been investigated by Devillers, Liang, Praeger and Xia in [26], where it is shown that apart from the two known symmetric 2-(16, 6, 2) designs, G is primitive of affine or almost simple type.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since then a special attention was given to the case λ > 1. A classification of the flag-transitive 2-designs with gcd(r, λ) = 1, λ > 1 and G AΓL 1 (q), where r is the replication number of D, has been announced by Alavi, Biliotti, Daneshkakh, Montinaro, Zhou and their collaborators in [2] and proven in [3], [4], [5], [9], [10], [8], [16], [17], [42], [52], [55], [56], [57], [58], [59], [60] and [61]. Moreover, recently the flag-transitive 2-designs with λ = 2 have been investigated by Devillers, Liang, Praeger and Xia in [26], where it is shown that apart from the two known symmetric 2-(16, 6, 2) designs, G is primitive of affine or almost simple type.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Thus i = 1, k 2 = q n −1 q−1 , and hence (n, q, k) = (4, 7, 20) or (5,3,11) again by [49], A8.1. If (n, q, k) = (4,7,20), then b = 21 • 20 • λ with λ | 20 and λ 2. However, P SL 4 (7) G P GL 4 (7) has no transitive permutation representations of degree b by [14], Tables 8.8-8.9.…”
Section: Reductions For X Based On Primitive Prime Divisors Of Its Ordermentioning
confidence: 99%
See 3 more Smart Citations